Teknik Pengelolaan Tenaga: Kajian dalam Koreografi Tunggal - Sarjiwo - (Institut Seni Indonesia Yogyakarta, 2010)
Power Management Techniques: A Study In Choreography Single Dance. This study aims to reveal thepower management techniques in a single choreographic works (solo dance). Data collection techniques used byobservation and interviews. Observations made by looking at and following the staging of activities undertakenby informants/interviewers. While, the interviews were conducted in a structured interview guide that has beenprepared to crawl processed data so that it can be more focused and directed. Collected data were analyzed byqualitative descriptive analysis techniques with management approach. According to this research it can beconcluded that, in order to make good quality of choreography character and good quality of dancer characteristicrequired planning process by conducting exercises diligently. Exercise is necessary for organisms of the body to becapable to performing its function as a medium for optimal expression of dance. The pattern of organization ormotion compotition could not be separated from the planning process that has been made. Each choreographerhas a different way with each other. Activities of implementation related to the power management at the timechoreography displayed, related to the ability of the dancers on the power control, regulate breathing pattern byplacing a breathing pattern as part of the choreography, and management of emotions that are not easily infl uencedby the presence of spectators. Evaluation is required at the time of the cultivation process and after the choreographyform was displayed. Evaluation is needed so that the creation that has been produced not quit on the spot.